High-wage workers and high-productivity firms: A regional view on matching in Germany - Philipp Ehrl (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2014)
This paper analyzes assortative matching between employers and employees and its interrelations with the employment density of local labor markets in Germany. I devote attention to the identiication of accurate quality measures: plants' total factor productivity and workers' fixed effect. Two different methods then yield evidence in favor of positive assortative matching. The correlation between both quality measures is positive. Wage gains amount up to 4% when both quality levels are equal. In a fairly general matching model, this shape of the wage curve arises due to complementarities of qualities in the production function. When generally higher productivities and wages in dense regions (caused by agglomeration economies and sorting) are not controlled for, the strength of matching and wage gains are overestimated. I also find that regional differences in matching quality cannot be attributed to the local density and unemployment rate.
Keywords: C78; J31; R11; 330; matching; agglomeration; unobserved skill; two-way fixed effects; TFP